Building Excellent Employee Performance through Motivation, Job Satisfaction, and Leadership - Larasati, Hilda (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
Leadership in an organization is usually said that leadership is a determining factor in the success or failure of an organization in achieving organizational goals as expected. The purpose of this study is to determine the influence between motivation, job satisfaction and leadership on employee performance. The method used in this study is quantitative which is descriptive analysis. In this study, the population is all employees or staff who work at Toko Bhakti Karya 1 Sawangan-Depok which amounts to 134 people. Using the Slovin sampling technique to find samples to be used to randomize respondents, so that the number of respondents in this study was 100 respondents. The results showed that the three factors, namely Motivation, Job Satisfaction, and Leadership, had a positive and significant influence on Employee Performance. That is, the higher the level of Motivation, Job Satisfaction, and Leadership, the higher the level of Employee Performance.